2011
DOI: 10.1124/jpet.111.186155
|View full text |Cite
|
Sign up to set email alerts
|

Hemokinin-1 Stimulates Prostaglandin E2 Production in Human Colon through Activation of Cyclooxygenase-2 and Inhibition of 15-Hydroxyprostaglandin Dehydrogenase

Abstract: Hemokinin-1 (HK-1) is a newly identified tachykinin, originating from the immune system rather than neurons, and may participate in the immune and inflammatory response. In colonic mucosa of patients with inflammatory bowel disease (IBD), up-regulation of the TAC4 gene encoding HK-1 and increased production of prostaglandin E 2 (PGE 2 ) occur. Our aim was to examine the mechanistic link between human HK-1 and PGE 2 production in normal human colon. Exogenous HK-1 (0.1 M) for 4 h evoked an increased PGE 2 relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…A potential explanation for these findings is that combined calcium and vitamin D supplementation may act synergistically to lower PTH concentrations, thereby reducing 1,25(OH) 2 D synthesis in the kidneys and calcium absorption in the gut, compared with the use of either supplement alone (49). While tumor-associated stromal cells, including fibroblasts and macrophages, may play an important role in tumor development by secreting cytokines and regulating PG-mediated inflammation via COX-2 expression (50), consistent with a previous study (51), we found COX-2 and 15-HPGD expression to be generally lower in the stroma than in the crypt epithelium of the morphologically normal colorectal mucosa. This may be due, in part, to there being fewer cells in the stroma than in crypts, and could explain why our estimated calcium and/or vitamin D treatment effects were less pronounced there.…”
Section: Discussionsupporting
confidence: 85%
“…A potential explanation for these findings is that combined calcium and vitamin D supplementation may act synergistically to lower PTH concentrations, thereby reducing 1,25(OH) 2 D synthesis in the kidneys and calcium absorption in the gut, compared with the use of either supplement alone (49). While tumor-associated stromal cells, including fibroblasts and macrophages, may play an important role in tumor development by secreting cytokines and regulating PG-mediated inflammation via COX-2 expression (50), consistent with a previous study (51), we found COX-2 and 15-HPGD expression to be generally lower in the stroma than in the crypt epithelium of the morphologically normal colorectal mucosa. This may be due, in part, to there being fewer cells in the stroma than in crypts, and could explain why our estimated calcium and/or vitamin D treatment effects were less pronounced there.…”
Section: Discussionsupporting
confidence: 85%
“…The gene sequence for NK 1 receptor in porcine genome is not published in NCBI, therefore, the primers for the NK 1 receptor were derived from sequences conserved across a broad range of mammalian species (human, cow, dog, and mouse). Gene expression was determined by quantitative real-time polymerase chain reaction (qRT-PCR) using the KAPA™ SYBR ® FAST kit as described (Liu et al, 2011; Dai et al, 2012). GAPDH was used as the housekeeping gene (HKG), and mRNA from an intact pig bladder tissue was used as the internal calibrator.…”
Section: Methodsmentioning
confidence: 99%
“…The discovery of the newest member of the tachykinin family, the hemokinin-1 (HK-1) encoded by the Tac4 gene [30], has given a new impetus to tachykinin research. HK-1 might be a novel key molecule in behavior, pain and inflammatory processes [31]. There is a growing amount of data regarding the mRNA expression of the Tac4 gene both in the central and peripheral nervous systems.…”
Section: Introductionmentioning
confidence: 99%